Six-phase doubly fed induction machine-based standalone DC voltage generator - Paweł Maciejewski; Grzegorz Iwański (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
The paper presents a multi-phase doubly fed induction machine operating as a DC voltage generator. The machine consists of a six-phase stator circuit and a three-phase rotor circuit. Two three-phase six-pulse diode rectifiers are connected to each three-phase machine section on the stator side and in parallel to the common DC circuit feeding the isolated load. The same DC bus is also common for the rotor side power electronics converter responsible for machine control. Two methods – direct torque control DTC and field oriented control FOC – were implemented for machine control and compared by means of simulation tests. Field oriented control was implemented in the laboratory test bench.